2017
DOI: 10.18203/2320-1770.ijrcog20171948
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological spectrum of gynecological pelvic masses: a cross-sectional study

Abstract: Background: Pelvic mass lesions are a commonly encountered entity in gynecological practice. These masses may be uterine or adnexal, benign or malignant. Clinicians have to be aware of their differential diagnosis to triage the patients and ensure optimum therapeutic approach. The objectives of this study were to study the diverse clinical spectrum of gynecological pelvic masses and to correlate the preoperative diagnosis based on clinical examination and ultrasonography with intraoperative surgical findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
2
1
Order By: Relevance
“…7 This study also concurred with other research by Pilli et al, Shobha S. Pillai, Batool et al, Sharma et al, and Bhagde et al, where abdominal pain was the most common symptom. 5,[8][9][10][11][12] However, the present study had fewer cases presenting as mass per abdomen compared to other studies. Pain abdomen was the most common symptom across all age groups except for women over 40 years of age, who presented with distension (50%) or menstrual abnormalities (50%).…”
Section: Discussioncontrasting
confidence: 52%
“…7 This study also concurred with other research by Pilli et al, Shobha S. Pillai, Batool et al, Sharma et al, and Bhagde et al, where abdominal pain was the most common symptom. 5,[8][9][10][11][12] However, the present study had fewer cases presenting as mass per abdomen compared to other studies. Pain abdomen was the most common symptom across all age groups except for women over 40 years of age, who presented with distension (50%) or menstrual abnormalities (50%).…”
Section: Discussioncontrasting
confidence: 52%
“…In study by Shobha S. Pillai. [16] 38 cases of leiomyomas were diagnosed preoperatively by physical examination and USG and 44 cases were confirmed by histopathological examination (HPE), showing a sensitivity of 95.5% and specificity of 61.4%. Study by Eze JC et al showed sensitivity of transvaginal scan (TVS) for diagnosis of uterine leiomyomas to be 94.5%, and specificity of 62.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Hard, irregular masses with restricted mobility increase the clinical suspicion of malignancy. As physical examination is not a reliable diagnostic tool as it has sensitivity of 51% USG has more pertinent role in initial diagnosis according to Shobha et al 8 . USG has many advantages being easily available and relatively inexpensive but a lot depends upon operator's experience 9 .…”
Section: Discussionmentioning
confidence: 99%